Spontaneous cluster activity in the inferior olivary nucleus in brainstem slices from postnatal mice - Rekling, J; Jensen, K; Jahnsen, H (2012)
A distinctive property of the cerebellar system is olivocerebellar modules, where synchronized electrical activity in neurons in the inferior olivary nucleus (IO) evokes organized activity in the cerebellar cortex. However, the exact function of these modules, and how they are developed, is still largely unknown. Here we show that the IO in in vitro slices from postnatal mice spontaneously generates clusters of neurons with synchronous Ca²⁺ transients. Neurons in the principal olive (PO), and the vestibular-related dorsomedial cell column (dmcc), showed an age-dependent increase in spontaneous calcium transients. The spatiotemporal activity pattern was occasionally organized in clusters of co-active neighbouring neurons, with regular (16 min⁻¹) and irregular (2–3 min⁻¹) repeating cluster activity in the dmcc and PO, respectively. IO clusters had a diameter of 100–170 μm, lasted ~1 s, and increased in occurrence from postnatal day P5.5 to P12.5, followed by a sharp drop to near zero at P15.5. IO clusters were overlapping, and comprised nearly identical neurons at some time points, and a varied subset of neurons at others. Some neurons had hub-like properties, being co-active with many other neighbours, and some were co-active with separate clusters at different times. The coherence between calcium transients in IO neurons decreased with Euclidean distance between the cells reaching low values at 100–200 μm distances. Intracellular recordings from IO neurons during cluster formation revealed the presence of spikelet-like potentials, suggesting that electrical coupling between neighbouring IO neurons may serve as a synchronizing mechanism. In conclusion, the IO shows spontaneous cluster activity under in vitro conditions, coinciding with a critical postnatal period in olivocerebellar development. We propose that these clusters may be forerunners of the ensembles of IO neurons shown to be co-active in adult animals spontaneously and during motor acts.